The redistribution of trade gains and the equity-efficiency trade-off - Marco de Pinto (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
The contribution of this paper is to derive an optimal redistribution scheme for trade gains in the case of a government's objective function that explicitly accounts for the equity-efficiency trade-off. The government pays unemployment benefits (UB) either financed by a wage tax, a payroll tax or a profit tax paid by exporters only. Using a Melitz-type framework with unionized labor markets and heterogeneous workers we show that there is a clear-cut ranking of the redistribution schemes in terms of welfare level: 1. UB financed by a profit tax paid by exporters, 2. UB financed by a wage tax, 3. UB financed by a payroll tax.
Keywords: F1; F16; H2; 330; trade liberalization; heterogeneous firms; trade unions; income inequality; unemployment benefits; taxes; Außenhandelsliberalisierung; Außenhandelsgewinn; Arbeitslosenversicherung; Einkommensumverteilung; Ertragsteuer; Exportindustrie; Theorie